Pengaruh Pengetahuan Perpajakan, Pengetahuan Akuntansi, dan Sikap Love of money Terhadap Kepatuhan Wajib Pajak UMKM Kuliner di Kota Padang - Sain, Muhammad Husain; Djefris, Dedy; Handayani, Desi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research aims to identify the impact of tax knowledge, accounting knowledge, and love of money attitudes on taxpayer compliance among Culinary MSMEs in Padang City. The study was conducted on MSMEs in Padang City, with a sample size 100. MSME actors were selected using a purposive sampling method. Data was collected by distributing questionnaires directly to MSME participants. The data analysis techniques included partial hypothesis testing with a t-test and simultaneous hypothesis testing using an F-test. The results of this case study indicate that tax knowledge has a positive effect, accounting knowledge does not have a significant effect, and the love of money attitude also does not significantly impact taxpayer compliance among Culinary MSMEs in Padang City.